Elastic fracture mechanics analysis of Bi-materials using boundary element method - Ang, Wee Kiang (2019)
This report presents the analysis of elastic fracture problem on bimaterial using the Boundary Element Method (BEM), with the aid of using the Boundary Integral Equation (BIE) programme. The iso-parametric element numerical formulation has been employed to obtain the stress intensity factor, K_1. Several modelling are presented to show the accuracy of the BIE program, and characteristic of the stress intensity factor of the crack tip that is embedded in the bimaterial plate. In all the analysis presented in this paper will neglect the body force and thermal effect. A bimaterial plate with embedded circular inclusion has been chosen to be analyses in this project. Analysis consists of the inclusion and the crack were subjected to various influences such as the distance, angle orientation, and different materials configuration. From the analysis, it is observed that a higher Stress Intensity Factor value is obtained when a soft inclusion is present and closer relative distance were chosen between the inclusion and the crack tip were. In addition, a trend of shielding/enhancement effect on the crack tip will be discussed with in this report.